Right ventricular involvement in breast cancer patients undergoing chemotherapy. (4th February 2022) - Ferri, L; Bergamini, C; Niro, L; Springhetti, P; Cerrito, LF; Schiavone, A; Dal Porto, M; Setti, E; Benfari, G; Rossi, A; Fiorio, E; Ribichini, FL
Abstract: Funding Acknowledgements: Type of funding sources: None. Background: Trastuzumab (TZ) and Anthracyclines (AC) are widely used for their key role in breast cancer. However, they may have different side effects on the cardiovascular system. One of the most concerning complications is myocardial dysfunction. Many studies have highlighted the importance of the screening for cardiotoxicity using left ventricular ejection fraction (LVEF) and global longitudinal strain (GLS). Nevertheless, there is little data about the right ventricular (RV) involvement. Purpose: Aim of this study is to analyze the modification of RV systolic function in this setting.  Methods: 105 women affected by HER-2 positive breast cancer treated with TZ referring to our echo-lab were enrolled in our single center prospective study. 3 patients were excluded due to an early TZ suspension not related to cardiovascular complications, thus 102 patients (97, 1%) were eligible for analyses. 86 of these (84, 3%) were treated also with AC. All patients underwent consecutive transthoracic echocardiography (TTE) before starting TZ and then every 3 months up to 12 months. 2D-Speckle tracking analysis was performed at baseline and at each examination using Tomtec software. A complete clinical evaluation was also performed at each follow up. LV systolic dysfunction was defined as an absolute reduction  of LVEF >10% from baseline to LVEF <53% or a relative reduction of GLS >15% from baseline and a reduction of LVEF >10% from baseline. RV systolic dysfunction was defined as TAPSE <17 mm, pulsed doppler S wave  <9, 5 cm/s and/or RV free wall strain <20%. Results: LV systolic dysfunction occurred in 11 patients (10, 8%).  TAPSE and pulsed doppler S wave remained within the normal limits in all patients at follow up. On the contrary, RV free wall strain was reduced in 11 patients (10, 8%), none of whom reported symptoms or signs of right-sided heart failure; 5 of these (45, 5%) also presented LV dysfunction . LV and RV systolic dysfunction occurred mainly at the same time.  Conclusions: Cancer treatment also appears to impact on right chamber myocardium. RV free wall strain analysis seems more reliable in detecting RV systolic dysfunction rather than clinical examination or common echocardiographic parameters, such as TAPSE or pulsed doppler S wave, in the setting of patients with breast cancer treated with chemotherapy. However, further studies are needed to investigate its prognostic role.